TEACHING WRITING DESCRIPTIVE TEXT BY USING REALIA MEDIA TO THE EIGHTH GRADE STUDENTS’ AT SMP NEGERI 9 PRABUMULIH - Delsi Arini; Mulyadi; Herlina (Esteem Journal of English Education Study Programme, 2024)
The aim of this research is to find out the effectiveness of using realia media in teaching descriptive text writing of students at SMP Negeri 9 Prabumulih. The research method used in this research is experimental with pre-experimental design. The research design used one-group pretest-posttest design. The samples of this research were 30 students consisting of 17 male students and 13 female students. Data collection techniques are done by tests. Tests are given at the pretest and the posttest. The results of this research indicate that realia media was effective to use in teaching writing descriptive text to the eighth grade students’ at SMP Negeri 9 Prabumulih. After the data from the pretest and the posttest were analyzed, the average results of the pretest were 62.8 and the posttest was 74.48. This is reinforced by the t test obtained tcount> ttable which is 5.254> 1.699 based on these results indicate Ha is accepted and Ho is rejected. So it can be concluded that realia media was effective to use in teaching writing descriptive text at SMP Negeri 9 Prabumulih.